Święci w kalendarzowej praktyce liturgicznej kościoła prawosławnego - Charkiewicz, Jarosław (Elpis, 2014)
The process of forming a church calendars in the context of placing the names of saints was an important part of the veneration of saints in the Orthodox Church. The establishment of the day or days of prayer to them was a long and complicated process. Despite of the general foreword, the article deals with initial part of that process, beginning from the edict of Milan of 313 up to 10th century. Author talks about the evaluation of the veneration of different types of the sanctity (holiness): martyrs, apostles, saint hierarchs of the Church, venerable (monastic), right-believing, unmercenary physicians, fool-for-Christ in calendar context. The placing of their names into so called diptychs initially was local. The lists of martyrs from diptychs (kind of ancients calendars) were presented during the service in the temples. Later, step by step, knowledge of these saints became wider and finally names of the saints found their place in calendar of whole Church. The article presents the best know ancient Church calendars, beginning from the lists of martyrs in the order of their death, i.e. Roman “Depositio martyrum” of the year of 354. Than it gives short outline of“ Chronograph” written by Furius Dionisius Filokalus, and wider review of “Syrian Martyrologium” of 362, which is sometimes called “the first all-Church calendar” and “Martyrologium Hieronimianum”, that was written in the middle of 5th century – a half of 6th century. The last calendar presented in the article is “Typicon of the Great Constantinople Church” written in 9th-10th century. Every next calendar had more and more names of saints in them. The author pay some attention to the differences between Western and Easter calendar of those times in the process of their development.